Formulation and Characterization of Peel-Off Gel Mask Containing Secang (Caesalpinia sappan L.) Wood Extract with Strong Antioxidant Activity - Cahyani, Intan Martha; Tanzaq, Tan Tanando; Agustina, Ruth Ditya; Setiawati, Kemala Endar (Tropical Biopharmaca Research Center, IPB University, 2025)
Secang (Caesalpinia sappan L.) wood contains flavonoid compounds such as brazilin, 3'-O-methylbrazilin, sappanin chalcone, and sappan chalcone, which act as primary and secondary antioxidants. Antioxidants are substances that can inhibit oxidation reactions by neutralizing free radicals. Enhancing the antioxidant potential of C. sappan wood can be achieved by developing a topical dosage form. Peel-off gel masks are an ideal form due to their ability to improve skin health and provide ease and comfort in application. This study aimed to formulate a peel-off gel mask containing C. sappan extract and evaluate its physical properties and antioxidant activity. The formulations were prepared using 2.5%, 5%, and 7.5% extract with sodium carboxymethyl cellulose, polyvinyl alcohol, and propylene glycol as the base. The resulting masks were assessed for physical characteristics (pH, viscosity, spreadability, adhesiveness, and drying time) and antioxidant activity using the DPPH method. The results indicated that increasing the extract concentration significantly (p < 0.05) increased viscosity, adhesiveness, and drying time, while decreasing pH, spreadability, and IC₅₀ value. All formulations demonstrated strong antioxidant activity (IC₅₀ between 50–100 µg/mL), with IC₅₀ values of 88.71 µg/mL, 81.58 µg/mL, and 79.04 µg/mL, respectively.